Performance measurement in airport settings: a systematic literature review - Bezerra, George C. L. (2016)
Purpose This study aims to provide a comprehensive overview of the literature related to performance measurement in airport settings. Two research questions were addressed: a. how the literature has evolved during the last forty-five years; b. which performance dimensions have been emphasized during this period. Design/methodology/approach For the purpose of this study, 380 documents, published between 1970 and 2015 were systematically analyzed. The literature reviewed comprises academic peer-reviewed articles, and studies published by other relevant sources, including professional-related literature. Findings The literature reviewed points to three stages relating to the evolution of the performance measurement in airport settings during the period analyzed. Although with a significant lag, this evolution seems to have followed the broad literature on performance measurement. Moreover, a relationship between these stages and the changes occurring at the airport industry was found. Several aspects of airport multidimensional performance are identified and discussed. Research limitations/implications Based on the findings of this study, it is concluded that a more comprehensive approach to airport performance measurement is needed. In this context, a research agenda is suggested. Practical implications The findings of this study have relevant practical implications for the airport industry. In this context, a framework representing a comprehensive approach to airport performance dimensions with impact on external stakeholders is presented. This framework can be a relevant contribution for researchers and practitioners which are looking for a more comprehensive and multidimensional approach to airport performance measurement. Originality/value To the best of our knowledge, this study appears to be the first to examine the literature related to airport performance measurement according to such a comprehensive approach. A framework of the performance dimensions related to the airport business is provided.